OPTIMIZATION OF PELTON TURBINE BUCKET DESIGN FROM COMPOSITE RESIN USING SOLIDWORKS - Damanik, Fadth Rizky; Fitri, Muhamad (Universitas Mercu Buana, 2023)
The Pelton turbine is a type of water turbine whose working principle utilizes the potential energy of water which is converted into kinetic energy through a nozzle. The fluid coming out of the nozzle push the bucket and rotates the Pelton turbine which ultimately produces electrical energy. Micro-hydro power plants that usually use Pelton turbines need to be developed to remote villages to meet electricity needs in Indonesia. Pelton turbine buckets, which are usually made of metal, are not only difficult to manufacture so they have to be specially ordered, but also easy to rust. Therefore, in this study, the bucket was made easier and simpler using an epoxy resin composite material reinforced with palm fiber. This makes it lighter and more corrosion resistant. The results of this study indicate that the epoxy composite fiber reinforced with 9% fiber volume has a higher tensile strength than the volume fraction 0%, 3%, 5%, 7%. The maximum tensile strength for 9% fiber content is 32.6054 N/mm2 . Then the tensile strength results are applied to the Pelton turbine bucket geometry with laboratory scale sizes that have been varied into 3 different size models in: bowl width (b), bowl height (h), and bowl height (h1). Based on solidworks simulation results all bucket models in this study have a factor of safety above the minimum limit of 6, therefore this composite can be used as a Pelton turbine bucket material. The first bucket version has a minimum factor of safety 6.656, the second bucket version has a minimum factor of safety 6.756, the third bucket version has a factor of safety 6.945.